Prevalence of work-related musculoskeletal symptoms of the neck and upper extremity among dentists in China. Issue 12 (19th December 2014) - Feng, Beibei; Liang, Qi; Wang, Yuling; Andersen, Lars L; Szeto, Grace
Abstract : Objectives: Studies from western countries show that dentists are vulnerable to work-related musculoskeletal disorders (WMSDs) of the neck and upper extremities, but little is known about their epidemiology among members of this rapidly growing profession in China. This study aims to investigate the prevalence of WMSDs and identify potential risk factors associated with their occurrence in the dental profession in China. Setting and participants: A cross-sectional survey was carried out in 52 different hospitals in a large metropolitan city in China. A total of 304 questionnaires were distributed to respondents identified via stratified random sampling and 272 dentists (121 females and 151 males) completed the survey. The response rate was 89.5%. Outcomes: Visual analogue score was used to record neck and upper limb musculoskeletal symptoms on a body chart. Work-related risk factors, including physical and psychosocial factors, were accounted for in the regression analysis. Results: 88% of the dentists reported at least one musculoskeletal disorder and 83.8% suffered from neck pain. In the multivariate analyses, working hours per day were associated with neck pain (OR=1.43; 95% CI 1.03 to 1.98). Inability to select the appropriate size of dental instrument was associated with shoulder (OR=2.07; 95% CI 1.00 to 4.32) and wrist/hand (OR=2.47; 95% CI 1.15 to 5.32) pain. As for psychosocial factors, high job demand was associated with symptoms in the shoulder (OR=1.09; 95% CI 1.00 to 1.18), elbow (OR=1.11; 95% CI 1.03 to 1.19) and wrist/hand (OR=1.09; 95% CI 1.02 to 1.17). Regular physical exercise was associated with decreased neck pain (OR=0.37; 95% CI 0.14 to 1.00). Conclusions: The prevalence of WMSDs among Chinese dentists is high. Specifically, long working hours, inability to select the appropriate size of dental instrument and high job demand are the most significant risk factors.